2011
DOI: 10.1016/j.bbrc.2011.06.061
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid synthesis is involved in autophagy in Saccharomyces cerevisiae

Abstract: In eukaryotes, autophagy is a conserved protein degradation system that degrades cytoplasmic components by encompassing them with double-membrane structures, called autophagosomes, and delivering them to the lytic compartments of vacuoles/lysosomes. Certain Atg proteins are known to be involved in autophagy, yet the identity and function of lipid molecules involved remain largely unknown. We investigated the involvement of sphingolipids in autophagy using Saccharomyces cerevisiae. Inhibiting synthesis of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…177 ), all or some of which may mediate autophagosome biogenesis and/or maturation. In support of this hypothesis, a recent study demonstrated that the inhibition of sphingolipid synthesis in Saccharomyces cerevisiae suppressed autophagosome biogenesis through a mechanism that was both independent of the Atg12-Atg5 and Atg8-PE conjugation systems as well as the formation of preautophagosomal structures (PAS), suggesting that sphingolipids play a critical role in the elongation, expansion, or closure of autophagosomal membranes ( 95 ). In addition, de novo ceramide synthesis is essential for autophagy following macrophage activation, and ceramide is observed to associate with autophagosomes in these cells ( 90 ).…”
Section: Downloaded Frommentioning
confidence: 93%
See 1 more Smart Citation
“…177 ), all or some of which may mediate autophagosome biogenesis and/or maturation. In support of this hypothesis, a recent study demonstrated that the inhibition of sphingolipid synthesis in Saccharomyces cerevisiae suppressed autophagosome biogenesis through a mechanism that was both independent of the Atg12-Atg5 and Atg8-PE conjugation systems as well as the formation of preautophagosomal structures (PAS), suggesting that sphingolipids play a critical role in the elongation, expansion, or closure of autophagosomal membranes ( 95 ). In addition, de novo ceramide synthesis is essential for autophagy following macrophage activation, and ceramide is observed to associate with autophagosomes in these cells ( 90 ).…”
Section: Downloaded Frommentioning
confidence: 93%
“…Endogenous ceramide species are critical for the induction of autophagy, as inhibition of CerS by fumonisin B1 or SPT by myriocin completely suppresses autophagy induced in response to short-chain ceramides and tamoxifen, respectively ( 85,88 ). Consistently, de novo synthesis is reported to be essential for the induction of autophagy in activated RAW264.7 cells ( 90 ) as well as in Saccharomyces cerevisiae ( 95 ). However, the mechanism and function of ceramideinduced autophagy remains unclear.…”
Section: Ceramidementioning
confidence: 97%
“…Immunoblot Analysis-Proteins were separated by SDS-PAGE and transferred to Immobilon TM polyvinylidene difluoride membrane (Millipore, Billerica, MA) as described previously (29). The membrane was incubated with anti-FLAG (M2, Stratagene), anti-HA (Y-11, Santa Cruz Biotechnology, Santa Cruz, CA; or 3F10, Roche Diagnostics), or anti-Pgk1 (Molecular Probes, Eugene, OR) antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were separated by SDS-PAGE and transferred to an Immobilon polyvinylidene difluoride membrane (Millipore, Billerica, MA) as described previously (24). The membrane was incubated with an anti-HA (16B12 [Covance, Princeton, NJ] or TANA2 [Medical & Biological Laboratories, Nagoya, Japan]), anti-GFP (JL-8; TaKaRa Bio, Shiga, Japan), anti-carboxypeptidase Y (anti-CPY) (Molecular Probes, Eugene, OR), anti-AID (BioROIS, Tokyo, Japan), or anti-Pgk1 (Molecular Probes) antibody.…”
Section: Methodsmentioning
confidence: 99%